2018
DOI: 10.1002/adma.201804437
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Chemotherapy and Immunotherapy against Breast Cancer Guided by Multiplexed Fluorescence Imaging in the Second Near‐Infrared Window

Abstract: to improve therapeutic effects and reduce recurrence of tumors. [3][4][5] Although there have been methodological advances, therapeutic schemes devised to challenge cancers are frequently thwarted due to the lack of correlation between the pharmacokinetics (PK) and pharmacodynamics (PD) of chemodrugs and transplanted immune cells in vivo, which results in inadequate drug/cell dosages and intervals and compromised therapeutic effects. Therefore, a visible method to objectively evaluate and therefore precisely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
88
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 41 publications
0
88
0
Order By: Relevance
“…[14] In recent years, interest in NIR-II contrast agents has increased. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] For PAI, the use of contrast agents with absorption at 1064 nm matches the output of Nd:YAG pulse lasers, has a higher American National Standards Institute (ANSI) safety limit for laser pulse power, and reduces scattering for deep tissue imaging. Many contrast agents have been explored for PAI at 1064 nm including copper sulfide [33] , semi-conducting polymers [34][35][36][37] , gold nanorods [38,39] and others.…”
mentioning
confidence: 99%
“…[14] In recent years, interest in NIR-II contrast agents has increased. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] For PAI, the use of contrast agents with absorption at 1064 nm matches the output of Nd:YAG pulse lasers, has a higher American National Standards Institute (ANSI) safety limit for laser pulse power, and reduces scattering for deep tissue imaging. Many contrast agents have been explored for PAI at 1064 nm including copper sulfide [33] , semi-conducting polymers [34][35][36][37] , gold nanorods [38,39] and others.…”
mentioning
confidence: 99%
“…2d). The Ag 2 S quantum dots also had stable and great photothermal effect under different laser power irradiations according to the previous study [43,[48][49][50][51]. The photoacoustic response of Ag 2 S@ BSA-SNO under certain wavelength was also examined by VEVO laser imaging system ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…[44][45][46][47] Second, owing to the emission of PSY shiing to the NIR-II channel (1.0-1.7 mm), high-quality images of precise diagnosis and therapy monitoring in vivo could be obtained with deep tissue penetration and at micronscale resolution. [48][49][50] Third, the utilization of F127 could not only endow PSY with excellent solubility and biocompatibility, 51,52 but also enable higher preferential accumulation of both P1 and SY1030 at tumor sites. 52 In contrast to the traditional Pt(II)-based drug cisplatin, our results demonstrated that the designed PSY nanoparticles exhibited a high level of tumor uptake with a superior signal to noise ratio (S/N) ratio for guiding therapy, enhancing the antitumor activities and lowering the adverse side effects in a U87MG tumor-bearing mice model.…”
Section: Introductionmentioning
confidence: 99%